Global perspectives for local action : using TIMSS to improve U.S. mathematics and science education : professional development guide (National Academy Press, 1999)
"Companion piece to the National Research Council's report, Global perspectives for local action: Using TIMSS* to improve U.S. mathematics and science education (NRC, 1999a). The guide, derived in part from the report and most usefully accompanied by it, is designed primarily for workshops for groups of education decision-makers--workshops that will support long-range efforts to improve K-12 student performance in mathematics and science"--Page xi